Suitability of a Semi-automatic Mobile System for Detecting Defects of Different Sizes and Shapes in Landfill Liners - Lopes, M. G. (2012)
Landfills are engineering facilities construct with a barrier system (lining system) intending to assure the protection of the environment. The effectiveness of lining systems depends, above all, of the performance of the GM. A critical issue on their performance is the defects caused from construction activities. Thus, a research program is in progress with the purpose of design a semi-automatic mobile system to assess the integrity of the GM after the placement of the PLCS, in a quick and accurate way, and overcome the disadvantages of the existing methods. The first stage of the research program is accomplished. At this stage, the functionality of a prototype was tested in a small scale pilot plant. This paper reports on the pilot plant on the results of tests carried out. Conclusions are drawn about the suitability of the prototype to detect holes of different sizes, shapes and at different spacing, as well as the influence of water content of the materials located below and above the GM.